Contrast sensitivity and visual acuity in subjects wearing multifocal contact lenses with high additions designed for myopia progression control. Issue 1 (February 2020) - Przekoracka, Katarzyna; Michalak, Krzysztof; Olszewski, Jan; Zeri, Fabrizio; Michalski, Andrzej; Paluch, Joanna; Przekoracka-Krawczyk, Anna
Highlights: Near visual acuity were not affected by high add (Add4) MFCLs (RELAX, SwissLens). Central contrast sensitivity decreased more significantly with Add2 MFCLs as compared to Add4 MFCLs Peripheral contrast sensitivity was impaired in a similar way by low and high add MFCLs. Visual performance was the same in subjects wearing MFCLs with 3 and 4.5 mm diameter central zones. Abstract: Objectives: To assess the visual performance of multifocal contact lenses (MFCLs) with high addition powers designed for myopia control. Methods: Twenty-four non-presbyopic adults (mean age 24 years, range 18–36 years) were fitted with soft MFCLs with add powers of +2.0 D (Add2) and +4.0 D (Add4) (RELAX, SwissLens) and single vision lenses (SVCL; Add0) in a counterbalanced order. In this double-masked study, half of the participants were randomly fitted with 3 mm-distance central zone MFCLs while the other half received 4.5 mm-distance central zone MFCLs. Visual acuity was measured at distance (3.0 m) and at near (0.4 m). Central and peripheral contrast sensitivity was evaluated at distance using the Gabor patch test. The area under the logarithmic contrast sensitivity function curve (ALCSF) was calculated and compared between the groups (i.e. different additions powers used). Results: Near and distance visual acuities were not affected by the lenses, neither Add2 nor Add4, when compared to Add0, however, CZ3 significantly reduced distance visual acuity with Add4 when compared to CZ4.5 (−0.08 logMAR vs. for CZ3 and -0.18 logMAR for CZ4.5, p = 0.013). MFCLs impaired central ALCSF only when Add2 was used (15.99 logCS for Add2 and 16.36 logCS for SVCLs, p = 0.021). Peripheral ALCSF was statistically lower for both addition powers of the MFCLs when compared to SVCLs (12.70 for Add2 and Add4, 13.73 for SVCLs, p = 0.009). The above effects were the same for both central zones used. Conclusions: MFCLs with CZ3 diameter and high add power (Add4) slightly reduced distance visual acuity when compared to CZ4.5 but no reduction in this parameter was found with medium add power (Add2). Central contrast sensitivity was impaired only by MFCLs with the lower add power (Add2). Both add powers in the MFCLs reduced peripheral contrast sensitivity to a similar extent.